Electroacupuncture Treatment for Post-Stroke Foot Drop: A Systemic Review of Randomized Controlled Trials - Hye Jeong Jo; Go Eun Chae; Hyun Woo Kim; Young Jin Lee; Ahra Koh; Ji Eun Choi; So Jung Kim; Woo Young Kim (MEDrang Inc., 2024)
A review of randomized controlled trials (RCTs) using electroacupuncture (EA) to treat patients with foot drop was performed to analyze the effectiveness of EA for this condition. Relevant studies (n = 183) from 7 databases (Cochrane Library, Excerpta Medica Database, PubMed, China National Knowledge Infrastructure, Korean Studies Information Service System, Research Information Sharing Service, and Oriental Medicine Advanced Searching Integrated System) were selected based on the inclusion and exclusion criteria, and 12 RCTs met the selection criteria. In all 12 studies, EA showed significantly positive changes. In most indicators, positive changes were observed in the EA group compared with that in the control group. Significant increases were confirmed in muscle strength-related indicators such as the Fugl-Meyer motor scale, surface electromyography, active range of motion, and gait-related indicators such as the Tinetti score, maximum walking speed, and Berg balance scale. No notable adverse events were reported. EA is suggested as an effective treatment for post-stroke foot drop; however, more RCTs are required.